Self-efficacy and positive thinking as predictors of health-related quality of life in women with stress urinary incontinence - Ching Hui Chien; Xuan Yi Huang; Shu Pen Hsu; Yi Hua Yen; Hun Shan Pan; Feng Chu Yen (BMC, 2022)
Highlights • General quality of life was influenced by positive thinking in women with SUI. • Health-related QOL was influenced by self-efficacy in women with SUI. • Symptom distress was a predictor of urinary incontinence-specific QOL. • Multi-element programs are needed to improve the health-related QOL of women with SUI.